2013
DOI: 10.1111/apha.12162
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of mitochondrial calcium uniporter prevents cardiac mitochondrial dysfunction caused by iron overload

Abstract: These findings strongly suggest that MCU could be the major route for iron uptake into cardiac mitochondria. The inhibition of MCU could be the novel pharmacological intervention for preventing iron-overload cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 85 publications
(145 reference statements)
2
56
0
Order By: Relevance
“…Although it is well established that iron-overload could induce apoptosis, its exact pathway in osteoblasts is still largely unknown. In iron-overload conditions, excess labile iron enters the mitochondria via the calcium uniporter, and then interacts with reactive oxygen intermediates leaked from mitochondrial respiratory chain through Fenton reactions, catalyzing powerful ROS to damage mitochondria (Chen et al, 2014; Sripetchwandee et al, 2014; Pelizzoni et al, 2011; Uchiyama et al, 2008). ROS catalyzed by labile iron elicits a range of detrimental effects in mitochondria, as following (1) impairment of mitochondrial respiratory enzyme activity; (2) decrease in ATP production; (3) loss of MMP; and (4) damage to mitochondrial DNA (mtDNA) (Ward et al, 2014; Mallikarjun et al, 2014; Al-Qenaei et al, 2014; Santambrogio et al, 2015; Rouault, 2016; Rines & Ardehali, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that iron-overload could induce apoptosis, its exact pathway in osteoblasts is still largely unknown. In iron-overload conditions, excess labile iron enters the mitochondria via the calcium uniporter, and then interacts with reactive oxygen intermediates leaked from mitochondrial respiratory chain through Fenton reactions, catalyzing powerful ROS to damage mitochondria (Chen et al, 2014; Sripetchwandee et al, 2014; Pelizzoni et al, 2011; Uchiyama et al, 2008). ROS catalyzed by labile iron elicits a range of detrimental effects in mitochondria, as following (1) impairment of mitochondrial respiratory enzyme activity; (2) decrease in ATP production; (3) loss of MMP; and (4) damage to mitochondrial DNA (mtDNA) (Ward et al, 2014; Mallikarjun et al, 2014; Al-Qenaei et al, 2014; Santambrogio et al, 2015; Rouault, 2016; Rines & Ardehali, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies showing that MCU could facilitate mitochondrial iron uptake. 15,39 Under normal conditions, Ca 2+ enters the mitochondrion through MCU. However, other anions such as Mn 2+ and Sr 2+ could also enter the mitochondrion via MCU because of the equal positive charges.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that only the MCU blocker RU360 could completely prevent iron overload-induced cardiac or brain mitochondrial dysfunction by decreasing ROS production, mitochondrial depolarization and swelling. However, the mitochondrial permeability transition pore (mPTP) blocker cyclosporin A (CsA) merely inhibits ROS production [72,73,74]. These results indicate that the MCU could be a major portal for mitochondrial iron uptake; however, the mechanism demands further study because there is no direct evidence that the MCU could transport iron into mitochondria.…”
Section: The Role Of the Mcu In Iron Overload-induced Mitochondriamentioning
confidence: 99%